2021
DOI: 10.1002/apj.2684
|View full text |Cite
|
Sign up to set email alerts
|

RF‐LSTM‐based method for prediction and diagnosis of fouling in heat exchanger

Abstract: Fouling degrades the thermal and hydraulic performances of the heat exchanger (HE), leading to failure if undetected. It occurs due to the accumulation of undesired material on the heat transfer surface. Knowledge about the HE fouling dynamics is required to plan mitigation strategies, ensuring a sustainable and safe operation. This paper aims to propose a feature‐based technique to predict the fouling status of the HE based on historical data. Three thermal and two hydraulic features are extracted from the HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It is determined using the temperature and flow rate profile at the shell and tube sides. In the proposed work, the RF‐LSTM (random forest‐based long‐term short‐term memory) based FR predictor reported in the literature is adopted to estimate the instantaneous FR 27 as in Figure 4. It uses the RF to select the optimal features based on the dominant effect of the HE operations.…”
Section: Methodsmentioning
confidence: 99%
“…It is determined using the temperature and flow rate profile at the shell and tube sides. In the proposed work, the RF‐LSTM (random forest‐based long‐term short‐term memory) based FR predictor reported in the literature is adopted to estimate the instantaneous FR 27 as in Figure 4. It uses the RF to select the optimal features based on the dominant effect of the HE operations.…”
Section: Methodsmentioning
confidence: 99%
“…The underlying root cause of fouling is the impurities in the inlet streams and their affinity for the heat exchanger surface. Unfortunately, the fouling cannot be measured directly in real-time; some of the available handheld devices support offline measurement that requires perforating the equipment ( [5], [6]). Notable studies investigated different heat exchangers and their fouling characteristics.…”
Section: Background -Fouling and Maintenance Of Heat Recovery Systemmentioning
confidence: 99%
“…The challenge is measuring the fouling thickness on the interior and exterior of the tubes. Real-time measurement is not possible to measure fouling readily; some of the available hand-held devices require dismantling the system, which is expensive, and regular measurement is not possible [6]. In such cases, leveraging thermodynamic models is very relevant for the user to generate system performance at various inlet, surrounding, and fouling conditions.…”
Section: Predictive Maintenance Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Te neural network model and a Kalman flter model are compared when applied for fouling detection, and from the result analysis, it is recommended to use the neural model to deal with fast drifts and the Kalman flter model to deal with slow drifts [17]. Fouling degrades the hydraulic and thermal performances of the heat exchanger, and if undetected, it will lead to failure of the system [18]. It has been concluded that the random forest (RF) with Gini index which is used to predict fouling resistance as a deep leaning neural network-based (LSTM, long short term memory) is a biased model [19].…”
Section: Introductionmentioning
confidence: 99%